Exploring Instructional Technology Tools and Resources for EFL Students - Hastomo, Tommy; Wirandani, Bimbi Ari; Yuliyani (IJLHE: International Journal of Language, Humanities, and Education, 2025)
Using instructional technology tools and resources is essential for English language teaching. This study was conducted to know the different instructional technology tools and resources used by English teachers for English language teaching. This paper's research design is a qualitative study. The researchers selected the purposive sampling method to administer the research sample. The research sample consisted of five SMA Negeri 4 Bandar Lampung English teachers. Semi-structured interviews were used in this study's data collection. In the present study, the data were qualitatively examined and summarized thematically. The results showed that English teachers employ a variety of materials and equipment, including a projector, laptop, sound system, digital textbook, and websites like YouTube and Instagram, to teach the English language. This result suggests that policymakers can utilize this study's findings to improve English learning quality by increasing learning tools and technologies.